Advancing Small Modular Reactor Technology Assessment in the Czech Republic, Egypt, and Poland - Waad Saleh; Dalibor Kojecky; Edyta Agata Macieja; Juyoul Kim (Science and Technology of Nuclear Installations)
This paper introduces the utilization of the International Atomic Energy Agency’s toolkit for reactor technology assessment (RTA) application to deploy small modular reactors (SMRs) in the Czech Republic, Egypt, and Poland. The increasing demand for clean energy has led to the prominence of small modular reactors (SMRs) in addressing global energy challenges. The successful integration of SMRs into national energy systems necessitates comprehensive evaluations that take into account each country’s specific characteristics and energy requirements. RTA application represents significant progress towards innovative nuclear solutions, advancing a cleaner and more resilient energy future plan. The aim of this study is assessing the feasibility and advantages of SMR implementation in these countries, focusing on energy security, emission reduction, and long-term sustainability. Various SMR technologies, including NuScale, SMART, HTR-PM, BWRX-300, SMR-160, and RITM-200, are comparatively analyzed based on safety, scalability, efficiency, and economic viability. The findings reveal that BWRX-300 suits the needs of the Czech Republic and Poland, while RITM-200 is the optimal choice for Egypt. Moreover, NuScale also stands as a strong alternative for all three countries. This article emphasizes the importance of informed discussions and evidence-based decisions, promoting sustainable energy development and global advancements in nuclear technology. By utilizing SMRs, the Czech Republic, Egypt, and Poland can enhance energy security, reduce emissions, and meet rising energy needs sustainably.